1961
DOI: 10.1063/1.1706354
|View full text |Cite
|
Sign up to set email alerts
|

Shock Initiation of Solid Explosives

Abstract: Initiation phenomena in solid explosives produced by strong shock waves are described. Shock pressures in the explosive are between 20 and 200 kbar. It is demonstrated that in the usual case the shock wave travels not as an inert shock, but as a shock to which the explosive contributes energy, probably from reaction at voids and defects. This slightly reacting shock travels at increasing velocity for some distance, typically 1 cm in the experiments described, and then in a travel of perhaps 0.01 cm becomes ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0

Year Published

1965
1965
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(102 citation statements)
references
References 7 publications
1
101
0
Order By: Relevance
“…They also showed that the intercept for zero particle velocity is the bulk sound velocity. The bulk velocity is defined by equation (1) c = (k/p )! …”
mentioning
confidence: 99%
“…They also showed that the intercept for zero particle velocity is the bulk sound velocity. The bulk velocity is defined by equation (1) c = (k/p )! …”
mentioning
confidence: 99%
“…The detonation behaviour of explosive materials is influenced by their microstructural features like particle size distribution, shape and surface area [1][2][3]. The secondary explosives developed with reduced particle size tend to be more insensitive for mechanical stimuli and may release energy with faster rate [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1960, Campbell et al [1] reported that a 3.9 GPa preshock desensitized a plasticbonded HMX explosive to initiation by a following 10 GPa shock. In a later study, Campbell and Travis [2] desensitized PBX-9404 and Composition B-3 by subjecting them to pre-shocks in the pressure range 1.0-2.4 GPa.…”
Section: Experimental Evidencementioning
confidence: 99%